2020
DOI: 10.1007/s11356-020-08832-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal exposure to NO2 on children’s neurodevelopment: a systematic review and meta-analysis

Abstract: The neurotoxicity of NO 2 exposure is well-known and potentially causes impaired of neural functions. This review aimed to estimate associations between prenatal NO 2 exposure and neurodevelopment for children. Articles published until May 2019 reported prenatal NO 2 exposure and children's cognition, psychomotor, language, attention, IQ, and behavior function were searched according to all related terms. The main databases we retrieved included PubMed, Web of Science, Embase, and Cochrane Library. Coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…29,30 In addition, exposure to NO 2 is associated with impaired psychomotor development after birth. 31 Pregnant females who lived closer to major roadways and are exposed to higher traffic-related pollutants have a higher risk of having a child with autism, decreased cognitive functions, and deficits in communication, memory, and attention functions. 8,22,32 A new cohort study also suggests pre-and postnatal exposures to pollution are associated with white matter microstructural changes (lower fractional anisotropy and higher mean diffusivity) in pre-adolescent years.…”
Section: Epidemiological Findings Linking Prenatal Exposure and Neuromentioning
confidence: 99%
See 2 more Smart Citations
“…29,30 In addition, exposure to NO 2 is associated with impaired psychomotor development after birth. 31 Pregnant females who lived closer to major roadways and are exposed to higher traffic-related pollutants have a higher risk of having a child with autism, decreased cognitive functions, and deficits in communication, memory, and attention functions. 8,22,32 A new cohort study also suggests pre-and postnatal exposures to pollution are associated with white matter microstructural changes (lower fractional anisotropy and higher mean diffusivity) in pre-adolescent years.…”
Section: Epidemiological Findings Linking Prenatal Exposure and Neuromentioning
confidence: 99%
“…59 Despite the mounting evidence suggesting that air pollution has deleterious effects on neurological development, it is important also to acknowledge that not all studies confirmed this association. 26,31,50,60 For example, in a recent systematic review/meta-analysis that examined the effects of fine particulate exposures on ADHD, three of the 12 studies that met inclusion criteria did not find any association. 60 The discrepancies in findings across some studies are probably a result of heterogeneity in various aspects of study design.…”
Section: 4142mentioning
confidence: 99%
See 1 more Smart Citation
“…Diffuse distributions of deficits, such as those we observed in this study, have been reported in studies of other neurotoxic exposures, with the possibility of some clustering around certain domains. 133 , 134 In particular, in this study, the outcome with the largest SMD was the subdomain of externalizing behavioral problems, which are commonly found in children with ADHD. 135 The increased rates of neurodevelopmental disorder and ADHD diagnoses is also consistent with studies of other neurotoxic exposures, specifically, children exposed to pesticides have reported behavioral problems, with 50% to 142% increased risks of ADHD and symptoms of hyperactivity.…”
Section: Discussionmentioning
confidence: 60%
“…In this older cohort (2002)(2003)(2004), representative for the Dutch speaking Flemish population, attention was paid to controlling for confounding factors, although not all confounding factors could be taken into consideration (e.g. the possible influence of air pollution on brain function) [29]. Analyses did not indicate bias by co-exposure of Pb and Cd, which were measured as ubiquitous neurotoxic environmental polluting metals in cord blood .…”
Section: Discussionmentioning
confidence: 99%